Proposed Terminology for Anal Squamous Lesions: Its Application and Interobserver Agreement Among Pathologists in Academic and Community Hospitals. Issue 1 (12th June 2017) - Roma, Andres A.; Liu, Xiuli; Patil, Deepa T.; Xie, Hao; Allende, Daniela
Abstract: Objectives: To analyze interobserver reproducibility and compare practice patterns between academic and community settings of Lower Anogenital Squamous Terminology (LAST). Methods: In total, 132 anal biopsy slides were revised as well as p16 immunostains. Results: LAST was used in 49% of cases (academic center, 68%; satellite hospitals [community practice setting], 32%). After pathology review and consensus interpretation, 23 (17%) case diagnoses were reclassified: eight (34.8%) cases (benign or low-grade squamous intraepithelial lesion [LSIL]) were upgraded to high-grade squamous intraepithelial lesion (HSIL) (p16 confirmed ordered during review); four (17.4%) cases originally classified as HSIL were downgraded to LSIL (p16 originally ordered in one case). There was no significant difference in discrepancies between original and consensus diagnosis in the community vs academic setting or by subspecialty (gynecological vs gastrointestinal). Overall interobserver agreement among reviewers was substantial (κ = 0.63) and improved with the use of p16 immunostain in challenging cases (κ = 0.71; P < .001). Conclusions: This new terminology is not yet uniformly used by pathologists in anal/perianal biopsy specimens; this two-tier system has a good interobserver agreement and is further improved with p16 use in appropriate cases.